Combustion characteristics of briquettes made from microwave-assisted co-pyrolysis products of palm shell and LDPE - Novi Caroko; Wahyudi Wahyudi; Haryo Wibowo (Journal of Engineering and Applied Technology, 2023)
Briquettes are solids that are generally made from agricultural waste materials. Char briquettes are one of the alternative energies for daily needs. This study used char from palm shell and LDPE microwave-assisted co-pyrolysis at 450 Watts. The briquettes were made from the product of co-pyrolysis of palm shell and Low-Density Polyethylene (LDPE) with variations in the composition of 0:100, 50:50, and 100:0 and pressure of 50 kg/cm2, 100 kg/cm2, 150 kg/cm2, and 200 kg/cm2. In this research, thermogravimetry analysis (TGA) was the method used to determine combustion characteristics. This study aimed to determine the combustion characteristics, including the Initiation Temperature of Fixed Carbon (ITFC), Initiation Temperature of Volatile Matter (ITVM), Peak of weight loss rate Temperature (PT), Activation Energy (Ea), and Mass Loss Rate (MLR). The results showed that the increased briquettes pressure increases the ITVM, ITFC, PT, and EA. The higher LDPE composition in the briquettes decreased the ITVM, ITFC, PT, and Ea, but increased the MLR.